Verbascum densiflorum at the UWM Field Station - (:unkn) unknown (My University, 1984)
Nine of 260 species of the Eurasian genus Verba scum have been reported from North America; only two (y. thapsus and y. blattaria) are common. Verba scum densiflorum is well established in the U.S. only in southeast Wisconsin in the area immediately surrounding the Field Station where it is an aggressive weed. It differs morphologically, phenologically and ecologically from either y. thapsus or y. phlomoides, the two more common species which it superficially resembles.
Keywords: Verbascum densiflorum; UWM Field Station